COMPARISON OF METHODS DRYING AND VARIETY FISH OF TESTING APPEARANCE ON DRIEDFISH TYPICAL ACEH (KEUMAMAH) - Ismail Sulaiman (BPFP Faperta UNIB, 2014)
Fresh fish processing into a dried fish is a fish processing has been done a long time, the processing of fish based traditional food processing becomes important to preserve cultural heritage in fish processing. Differences drying method in the processing can affect the taste and texture of the fish produced timber. Types of tuna used significantly different to the color produced on the dried fish . The water content produced in this study is 15:57 (w/w %), ash content 1 , 58 ( % ), mean organoleptic test (color: 3.3, taste and smell 3:35, aroma : 3:34). Preferred types of fish are tuna and the most preferred method oven method.Keyword :